2021
DOI: 10.1371/journal.pone.0254492
|View full text |Cite
|
Sign up to set email alerts
|

The last will: Estate divisions as a testament of to whom altruism is directed

Abstract: We use data on estate divisions to study to whom altruistic preferences are directed. Insofar bequests are given without the prospect of future personal benefits in mind, they are presumably intrinsically motivated. Hence, estate divisions provide a rare opportunity to study intrinsically motivated prosocial behavior in the field. The empirical analysis is based on data from digitized estate reports for all individuals in Sweden who passed away in 2002 and 2003. The data show in detail how the decedents distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Some empirical results support this assumption. Elinder, Engström and Erixson (2021) analyzed estate divisions in Sweden and found family members, both by blood and partner, receive the lion's share of the estates but that other relatives, friends, and charities receive only very small shares. Tilse et al (2015) reported very similar findings from a survey in Australia asking for intentions stated in wills.…”
Section: Theories Of Intergenerational Transfersmentioning
confidence: 99%
“…Some empirical results support this assumption. Elinder, Engström and Erixson (2021) analyzed estate divisions in Sweden and found family members, both by blood and partner, receive the lion's share of the estates but that other relatives, friends, and charities receive only very small shares. Tilse et al (2015) reported very similar findings from a survey in Australia asking for intentions stated in wills.…”
Section: Theories Of Intergenerational Transfersmentioning
confidence: 99%